Evaluation on the effectiveness of LestaniTM in oil palm estates (a field trial) - Chong, Khim Phin; Markus Atong; Ridzwan Abdul Rahman (Universiti Malaysia Sabah, 2010)
This research project was conducted at two sites; SPL Research Laboratory 1 in UMS and Sawit Kinabalu Sdn Bhd's Langkon Estate at Kota Marudu, Sabah. This research project was carried out from March 2011 to December 2011. It took approximately nine months. Observation period for this field trial is five months (July 2011 to December. 2011). The objectives of this project are to validate the effectiveness of LesTaniTM in controlling Basal Stem Rot (BSR) in oil palm estates and determine the suitable concentration of the LesTaniTM to be used in suppressingt he disease severity of BSRi n field. Four concentrationso f LesTaniTMwe re tested; 0.4 g a.i , 0.8 g a.i , 1.2 g a.i and 1.6 g a.i . Each concentration of LesTaniTMte sted was consisted of four replicates with one palm for each replicate. Infected palms with similar BSR disease intensity, age, soil topography and condition were selected for the trial. There were two controls in the trial. The controls were the healthy palms with no treatment and palms infected by G. boninense but not treated with any treatment. The assessments on the effectivenesso f LesTaniTM were based on the isolation of fungus on Ganoderma Selective Medium (GSM), ergosterol content from infected tissues and Colony Forming Unit (CFU). Completely Randomized Design (CRD) was chosen as the experimental design for this field trial. One-Way ANOVA was calculated at 5% significance level by using SPSS 17.0 (Statistical Package for Social Science software) for the data analysis. Data was subjected to analysis variance, differences was compared using a Tukey test at a significance of P<0.05. For the isolation of fungus on Ganoderma Selective Medium (GSM), the fungi which were successfully grew on the GSM after 15 days were identified as G. boninense. While for the Colony Forming Unit (CFU), there was no colony of G. boninense form on the GSM after observation for one month. In this study, no ergosterol was found in healthy palms but in contrast ergosterol were detected in infected tissues before and after the treatments of varies concentration of LesTaniTM. The control (infected palms; without treatment) resulted on significantly higher mean score of ergosterol (0.6395 pg g-1) at p<0.05 compared to palms treated with different concentration of LesTaniTML. esTaniTM(0 .4 g a.i ) had the lowest mean score of ergosterol, followed by LesTaniTM(1 .2 g a.i ), LesTaniTM(0 .8 g a.i ) and LesTaniTM(1 .6 g a.i ). This indicated that all of the different concentrations of LesTaniTMre duced the ergosterol content in bole tissues of infected palms. Although LesTaniTMw ith 0.4 g a.i had the lowest amount of ergosterol (-0.4379 pg g-1) but there was no significant difference between this treatment with other concentrations; 0.8 g a. i, 1.2 g a. i and 1.6 g a.i at p<0.05. LesTaniTM with different concentration were found effective with no significant among them suggesting the lowest concentration of 0.4 g a. i maybe chosen for future application in order to reduce the cost production of LesTaniTM for marketing purpose.